2019
DOI: 10.1017/age.2019.24
|View full text |Cite
|
Sign up to set email alerts
|

International Trade Implications of Highly Pathogenic Poultry Disease Events

Abstract: Animal disease events can lead to international trade restrictions which can vary in duration, products included, and geographical extent. Accounting for multilateral resistance between trading partners, a general gravity model of trade is estimated with a Hausman-Taylor and a Hausman-Taylor seemingly unrelated estimator to evaluate the trade quantity impact by commodity resulting from highly pathogenic poultry disease events in 24 exporting markets. Commodity specific results show that quantity traded and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Through use of a gravity model it found that regions of the most extensive inventory are more likely to trade with each other, regardless of distance than those with small populations [ 23 ]. Researchers have also used augmented gravity modeling to assess the impact of disease outbreaks in the US on poultry and poultry product trade [ 31 ]. Both studies show that the gravity model’s use could quantify various impacts on an industry, such as disease, on bilateral trade.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through use of a gravity model it found that regions of the most extensive inventory are more likely to trade with each other, regardless of distance than those with small populations [ 23 ]. Researchers have also used augmented gravity modeling to assess the impact of disease outbreaks in the US on poultry and poultry product trade [ 31 ]. Both studies show that the gravity model’s use could quantify various impacts on an industry, such as disease, on bilateral trade.…”
Section: Introductionmentioning
confidence: 99%
“…While augmented gravity models have been used exhaustively for international and local trade agreements, their application to understanding animal marketing is limited and within swine nonexistent. While some work exists [ 23 , 31 ], none have focused on movement within the US swine industry. This study implements the augmented gravity model to study the effects of regionalized standstills on animal movement in the cull sow marketing channel.…”
Section: Introductionmentioning
confidence: 99%